Use Possibilities of “Diverse Democracy” Forms under Modern Russia Conditions: Constitutional Principles and Political Reality - R. M. Vulfovich (Теоретическая и прикладная юриспруденция)
In the 21st century the place and role of different social institutions changes essential. An independent and self-sufficient person becomes in a greater measure a political actor and demands the participation right enlargement not only in public activities but in the decision making about the main issues of his / her life. It leads under the informatization and digitalization conditions to the rapid individual actions’ volume growth and to the individual rationality increase which can have positive and negative consequences as well.The local self-government — the nearest institute to citizens able to channel best of all others their needs — is also inside the transformation process. In Russia the above described processes develop in the more complicated and inconsistent context and require more attention to the decisions about self-government issues. The really acute manifestation of them is connected with a poor understanding in the society of a self-government role and place in the optimal and uniform quality of life providing on municipalities’ territory. At the time the Constitution of the Russian Federation is the solid foundation for localities functioning but it also consists of some contradictions.New local self-government development tendencies in more developed systems with a longer history appear in multiple forms called in some actual research “diverse democracy”. Its meaning can become in a near future the crucial meaning.